Purification and characterization of Escherichia coli heat-stable enterotoxin II. - Fujii, Y (1991)
Escherichia coli heat-stable enterotoxin II (STII) was purified to homogeneity by successive column chromatographies from the culture supernatant of a strain harboring the plasmid encoding the STII gene. The purified STII evoked a secretory response in the suckling mouse assay and ligated rat intestinal loop assay in the presence of protease inhibitor, but the response was not observed in the absence of the inhibitor. Analyses of the peptide by the Edman degradation method and fast atom bombardment mass spectrometry revealed that purified STII is composed of 48 amino acid residues and that its amino acid sequence was identical to the 48 carboxy-terminal amino acids of STII predicted from the DNA sequence (C. H. Lee, S. L. Mosely, H. W. Moon, S. C. Whipp, C. L. Gyles, and M. So, Infect. Immun. 42:264-268, 1983). STII has four cysteine residues which form two intramolecular disulfide bonds. Two disulfide bonds were determined to be formed between Cys-10-Cys-48 and Cys-21-Cys-36 by analyzing tryptic hydrolysates of STII.